The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1001/jamapsychiatry.2019.4475
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Task-Shifted Trauma-Focused Cognitive Behavioral Therapy for Children Who Experienced Parental Death and Posttraumatic Stress in Kenya and Tanzania

Abstract: IMPORTANCE Approximately 140 million children worldwide have experienced the death of one or both parents. These children, mostly in low-and middle-income countries, have higher rates of mental health problems than those who have not experienced parental death. Cognitive behavioral therapy (CBT) may improve the well-being of these children, but to our knowledge there have been no randomized clinical trials specifically focused on this population.OBJECTIVES To test the effectiveness of trauma-focused CBT (TF-CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(129 citation statements)
references
References 44 publications
3
118
0
Order By: Relevance
“…"Building and Sustaining Interventions for Children (BASIC): Task Sharing Mental Health Care in Low-Resource Settings" builds on our 15-year history of collaborations with Ace Africa in Kenya, and recent work evaluating the effectiveness of Trauma-focused Cognitive Behavioral Therapy (TF-CBT) [19] ("Pamoja Tunaweza") with children who experienced parental death [20,21] and have mental health impact. Our goal is to identify locally sustainable implementation policies and practices (IPPs) that lead to effective implementation of task-shifted EBT delivery (Pamoja Tunaweza in this study) in 2 governmental sectors in Kenya, identified by our Kenyan partners as potential platforms for scaleup-Education (via teacher delivery) and Health (via community health volunteer [CHV] delivery).…”
Section: Conceptual Framework/approachmentioning
confidence: 99%
“…"Building and Sustaining Interventions for Children (BASIC): Task Sharing Mental Health Care in Low-Resource Settings" builds on our 15-year history of collaborations with Ace Africa in Kenya, and recent work evaluating the effectiveness of Trauma-focused Cognitive Behavioral Therapy (TF-CBT) [19] ("Pamoja Tunaweza") with children who experienced parental death [20,21] and have mental health impact. Our goal is to identify locally sustainable implementation policies and practices (IPPs) that lead to effective implementation of task-shifted EBT delivery (Pamoja Tunaweza in this study) in 2 governmental sectors in Kenya, identified by our Kenyan partners as potential platforms for scaleup-Education (via teacher delivery) and Health (via community health volunteer [CHV] delivery).…”
Section: Conceptual Framework/approachmentioning
confidence: 99%
“…Data for this study come from a large NIMH-funded hybrid effectiveness-implementation study of TF-CBT delivered through both the Education (via teachers) and Health (via CHVs) sectors in Western Kenya: Building and Sustaining Interventions for Children (BASIC; NIMH-funded R01MH112633) conducted as a collaboration between Duke University, the University of Washington, and Ace Africa, in Bungoma, Kenya (33). This study builds on a pilot of TF-CBT in East Africa (31) and a large randomized controlled trial (RCT) in Kenya and Tanzania (30) that demonstrate the effectiveness of lay counselor-delivered TF-CBT in Kenya. The goal of BASIC is to learn what makes an enabling context for mental health delivery in both Education and Health, by identifying implementation practices and policies (IPPs) that support successful implementation in the distinct sectors.…”
Section: Building and Sustaining Interventions For Children (Basic) Omentioning
confidence: 99%
“…Intervention TF-CBT is an evidence-based treatment protocol which treats psychosocial sequelae from child trauma exposure, with a specific application for maladaptive grief (23). There is substantial evidence of its effectiveness from RCTs in highincome countries (HICs; 35) with evidence of effectiveness from large RCTs in Zambia (15) and Kenya (30) and two small RCTs in the Democratic Republic of Congo (36,37). In our previous collaborative work, we modified TF-CBT for delivery in Eastern Africa, with results from an open trial in Tanzania suggesting that the intervention held promise, given positive clinical outcomes at the end of treatment and maintained gains at a 1-year follow up (31).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations